Case Study : Edda Collection Sdn. Bhd. / Raudhah Ab. Rahman - Ab. Rahman, Raudhah (2020)
Edda Collection is a company that sells Muslimah fashion clothing also do a sewing services in the shop. They sell a lot of islamic clothes and accessories that suit local people. In addition, men's clothes like baju melayu are also available in their boutique. I use the SWOT approach to help solve the problem and to define the problem with the answer that can be made by the organization itself. The biggest challenge faced by Edda Collection is the lack of machine and manpower. The organization should employ more skilled staff to assist with the production of products. In addition, they should set up a new machine to help production staff manufacture products more quickly and conveniently, other than that the organization should employ more sales assistants to ensure that they fulfill the standards of their products.